The Effect of Problem-Based Learning and E-Modules on Student Motivation and Learning Outcomes in Hydrocarbons - Alexander Robert Junianto Lumban Gaol; Bajoka Nainggolan; Henny Batu Bara (Universitas Negeri Medan, 2025)
This research conducted at SMA Negeri 2 Doloksanggul aims to: (1) determine the effect of the Problem-Based Learning (PBL) model assisted by E-Modules (4D) on improving student learning outcomes in hydrocarbon topics; (2) assess the influence of this model on increasing student learning motivation; and (3) examine the correlation between learning motivation and improved learning outcomes. Student learning outcomes in Experimental Class I improved by 82.29%, while in Experimental Class II, the improvement was 78.06%. Motivation scores averaged 79.94% in Experimental Class I, compared to 74.89% in the control class. The correlation test revealed a significant positive relationship between motivation and learning outcomes, with rtable < rcount (0.674 < 0.744), thus confirming that increased motivation contributes to improved academic performance. These findings support the use of E-Module-assisted PBL as an effective approach to enhance both student motivation and learning outcomes.